2020
DOI: 10.1080/09699260.2020.1826778
|View full text |Cite
|
Sign up to set email alerts
|

Improved parent–child communication following a RCT evaluating a legacy intervention for children with advanced cancer

Abstract: Although legacy-building is a priority for quality palliative care, research has rarely examined effects of legacy interventions in children, particularly their impact on parent-child communication. We examined the impact of a web-based legacy intervention on parent-child communication. Facebook advertisements were used to recruit families of children (ages 7-17) with relapsed/refractory cancer. Parent-child dyads were randomly assigned to the intervention or usual care group. The intervention website guided c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“… 18 This discrepancy between quantitative and qualitative results has been seen in our previous work as well as on other main outcomes of this study reported elsewhere. 15 , 20 Previous studies have suggested that legacy interventions may improve emotional dimensions of QOL and communication. 12 , 15 The PedsQL may not be the best measure to capture effects of our intervention, and QOL as operationalized by the PedsQL may not be the exact outcome influenced by our intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 This discrepancy between quantitative and qualitative results has been seen in our previous work as well as on other main outcomes of this study reported elsewhere. 15 , 20 Previous studies have suggested that legacy interventions may improve emotional dimensions of QOL and communication. 12 , 15 The PedsQL may not be the best measure to capture effects of our intervention, and QOL as operationalized by the PedsQL may not be the exact outcome influenced by our intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Parent-child communication is not only a key area for future research but also a key area of refinement needed for our intervention based on parent feedback that the intervention served as a communication tool and positive intervention effects on child-father communication. 20 The discrepancy between child and parent proxy reports regarding worry highlights the need for pediatric research to involve multiple informants, including children, mothers, and fathers. While it is not uncommon for pediatric palliative care studies to sample child-parent dyads, 2 , 21 or mothers and fathers of seriously ill children, 22 studies rarely have included reports directly from all three: ill children, mothers, and fathers, something critical to implementing effective family-centered palliative care interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Children near the end of life often desire to do or say things to be remembered, yet cognitive or verbal impairments can preclude these children from participating in services which facilitate documentation of their legacies [ [66] , [67] , [68] ]. Legacy-making has been explored in both adult and pediatric populations [ 32 , 33 , 66 , [68] , [69] , [70] , [71] , [72] ]. Legacy-making in adults has been shown to increase patients' sense of dignity, purpose, meaning, and will to live, while decreasing suffering and depressive symptoms [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Legacy-making in adults has been shown to increase patients' sense of dignity, purpose, meaning, and will to live, while decreasing suffering and depressive symptoms [ 72 ]. Our work has shown that legacy-making can improve psychological distress, physical symptoms, and family components (quality of communication) among children with cancer (ages 7–17) and their parents [ 32 , 33 , 67 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Other results related to the webbased legacy intervention have been reported elsewhere. [24][25][26][27][28]…”
Section: Design and Methodsmentioning
confidence: 99%